Schirrous invasive ductal carcinoma of the breast overexpress p53 oncoprotein - Ferrini, Flávia Silva; Rossi, Marcos Antonio; Mourão Neto, Mário; Soares, Fernando Augusto (São Paulo Medical Journal, 2001)
CONTEXT: Breast cancer is the most important neoplasm in adult women, and its worldwide incidence is growing. The tumoral stroma is very important for modulating the growth and invasion of the tumor itself. The relationship between these two components is not completely understood. Schirrous carcinoma is a variant of ductal invasive carcinoma in which the stroma is very desmoplastic, and the importance of this finding still a motive for debate in the literature. OBJECTIVE: To compare the desmoplastic reactions against biological markers, such as estrogen and progesterone receptors, oncoprotein c-erbB-2 and oncoprotein p53, with the objective of studying the relationship between the tumoral stroma and epithelial cancer cells. TYPE OF STUDY: Retrospective study. SETTING: Cancer Hospital A C Camargo and Faculty of Medicine of Ribeirão Preto, University of São Paulo, São Paulo, Brazil. SAMPLE: 107 adult women operated because of ductal invasive carcinoma. The cases were separated into 4 groups according to the desmoplastic reaction – less than 15%, between 15-50%, 51-85%, and more than 85% fibrosis. The grade of fibrosis was determined by picrus-sirius staining and quantified by using a microscope with a stereo-imaging grid. Immunohistochemical methods were used to determine the expression of the hormonal receptors and c-erbB-2/p53 oncoprotein. MAIN MEASUREMENTS: Extent of desmoplastic reaction versus expression of estrogen and progesterone receptors, oncoprotein c-erbB-2, and oncoprotein p53. RESULTS: The results showed that schirrous carcinoma expresses oncoprotein p53 more frequently than other carcinomas with less extensive desmoplastic reaction. There were no differences between the grade of fibrosis and the other biological markers. CONCLUSION: The intense stromatous reaction in invasive ductal carcinoma may modulate the expression of p53. Further investigations should be made with the aim of understanding how this expression determines the proliferative activity in schirrous carcinoma, and whether this overexpression is secondary to mutation of the p53 gene or due to modulation of other molecules of the stroma.